Aligning policy and law? The creation of a domestic abuse offence incorporating coercive control - Brooks-Hay, Oona (2018)
Since 2000, the Scottish Government has adopted a gendered definition of domestic abuse which explicitly positions it as both a cause and a consequence of gender inequality. Following the launch of a new strategy to prevent and eradicate violence against women and girls, the Scottish Government announced proposals to create, for the first time, a bespoke offence of domestic abuse, designed to encompass the spectrum of abusive acts that constitute domestic abuse, including emotional and psychological abuse. The new offence is intended to better reflect the experience of victims subject to coercive control, improve the criminal justice response and facilitate access to justice. It represents one of the most radical attempts yet to align the criminal justice response with contemporary policy and feminist conceptual understanding of domestic abuse as a form of coercive control. Drawing on feminist scholarship which has interrogated the value of law reform, we critically assess the scope of the legislation, the likely challenges associated with its use in the Scottish context, and the potential for unintended consequences